The effect of jigsaw strategy and mastery learning modules on mathematics students' attitude and achievements in Nigerian schools - Yemi, Tukur Madu (2019)
The persistent poor Mathematics achievement in Nigeria's secondary schools is an issue that has long been a concern of the Federal Government of Nigeria. Hence, it is necessary to carry out continuous research on effective teaching strategies so that it can contribute to the improvement of Mathematics achievement in Nigeria. Mathematics teachers in Nigeria have long been complacent to teach Mathematics using the conventional approach. This approach has been influencing Nigerian students' attitude towards mathematics and their mathematics achievement. This study aims to determine the effect of Jigsaw Strategy and Mastery Learning Modules on attitude towards mathematics and their mathematics achievements among secondary schools students in Nigerian. This study used mixed methods. A Nonequivalent controlled pre-test post- test quasi-experimental design was used to collect the quantitative data via Mathematics attitude and Mathematic achievement test. The qualitative data was collected via interviews and observation checklist. The target population of this study was 590 I Senior Secondary School One (SSI) Students in Gombe State, Nigeria. A total of 120 SSI students had participated in this study and they were divided into two treatment groups and one control group. The first and second treatment groups were respectively taught Mathematics using the Jigsaw and Mastery Learning (JSML) approach and the Jigsaw Strategy (JS) approach. The control group was conventionally taught. The quantitative data were analyzed using Analyses of Covariance (ANCOVA) while the qualitative data was thematically analyzed. The findings show that there was improvement in the JSML and JS groups' Mathematics scores. The JSML group students achieved better than their JS group counterparts and a statistically significant difference was observed between the control and treatment groups (p< .05) in the Mathematics Topics post-test and the attitude post- test scores. The qualitative data revealed favorable responses from the teachers towards the use of modules for JSML and JS groups. Majority of the students had positive attitude towards Mathematics which contributed towards the increase in Mathematics achievement.